The Effect Of Tuber Cutting And Soaking Time GA3 On Growth Of Shallots (Allium Cepa L.) Hydroganically By Using Used Bottles - Nasrullah Fahmi Ridho; Agus Sugianto; Siti Asmaniyah (AGRONISMA, 2022)
The purpose of this study was to determine the growth of shallots. The research was conducted in the green house of the Faculty of Agriculture, Islamic University of Malang with an altitude of 526 meters above sea level, a temperature of 22 C and an air humidity of 98%. This study used a factorial randomized block design (RAK) consisting of 2 factors, the first factor was cutting the tubers with 2 levels, namely: without cutting the tubers and cutting the tubers in parts, the second factor was the length of soaking time which consisted of 4 levels, namely: without soaking, soaking 40 minutes, soaking 80 minutes and soaking 120 minutes. The results showed that in general there was no significant interaction between the length of the tuber cutting treatment and the immersion time of GA3. However, separately the GA3 immersion time treatment had a significant effect on plant length of 27.92 cm, leaf area of 11.96 cm2 and total root length of 599.09 cm. The treatment of cutting tubers had no significant effect on all parameters at all ages of observation.